Prospective quality of life assessment between treatment groups for oral cavity squamous cell carcinoma. Issue 6 (2nd September 2013) - Ch'ng, Sydney; Oates, Justine; Gao, Kan; Foo, Kerwyn; Davies, Sarah; Brunner, Markus; Clark, Jonathan R.
Abstract Background Postoperative radiation therapy (PORT) is frequently recommended to improve survival outcome. The effect of PORT‐associated morbidity on patients' quality of life (QOL) is, however, not well established. This study assessed the effect of PORT on medium‐term (ie, at 6 months) QOL in patients with oral cavity squamous cell carcinoma (SCC). Methods Patients completed the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ‐C30) and Quality of Life Questionnaire Core Head and Neck 35 (QLQ‐HN35) at initial presentation, and at 3‐, 6‐, and 12‐month follow‐up. Baseline QOL scores were adjusted for using analysis of covariance (ANCOVA). Results Global health status (mean difference = 13.3; p = .042) and xerostomia (mean difference = 35.4; p = .003) were significantly worse at 6 months in patients who received PORT compared to those treated with surgery alone. Conclusion The survival advantage needs to be balanced against increased treatment toxicity. PORT is associated with reduced global health status, increased xerostomia, and marginally increased levels of fatigue at 6 months posttreatment for oral cavity cancer. © 2013 Wiley Periodicals, Inc. Head Neck 36: 834–840, 2014